Characteristics of peripheral blood Gamma-glutamyl transferase in different liver diseases. Issue 1 (7th January 2022) - Xing, Mindan; Gao, Min; Li, Jia; Han, Ping; Mei, Ling; Zhao, Lili
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Gamma-glutamyl transferase (GGT) is a marker of oxidative stress and cholestasis. Because of its low specificity, clinicians usually ignore its diagnostic value. To compare and analyze the clinical features of GGT in primary biliary cholangitis (PBC), drug-induced liver injury (DILI), alcoholic liver disease (ALD), and non-alcoholic fatty liver disease (NAFLD) from the perspective of different causes instead of the severity of the disease. We observed the distribution characteristics and the rate of abnormality of GGT in the above 4 diseases. The relationship between GGT and alanine aminotransferase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), total serum bilirubin, triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol, high-density lipoprotein cholesterol was analyzed using Spearman correlation. The highest level of GGT was up to 1000.00 to 2000.00 U/L in PBC and DILI, and the highest level of GGT was more than 2000.00 U/L in ALD, yet the difference was not statistically significant ( P  > .05). The highest level of GGT was only about 200.00 U/L in NAFLD and was the lowest in 4 liver diseases. Also, GGT was positively correlated with ALP, TC in PBC and DILI. Also, in ALD, GGT was positively correlated with ALT, AST, ALP, TG, and TC. In NAFLD, GGT was positively correlated with ALT, AST, and TG. The abnormal GGT in PBC and cholestasis DILI was associated with cholestasis; in ALD, it was associated with oxidative stress and cholestasis, and in NAFLD, it was associated with oxidative stress. GGT levels had different characteristics in different liver diseases, which were closely related to the pathogenesis of liver diseases.